(untitled) (CIPEEX, 2022)
TO REPORT THE EXPERIENCE OF THE EXPERIENCE OF THE STUDENTS INSERTED IN THE LABORATORY OF ANALYSIS OF HUMAN MOVEMENT PARTICIPATING IN THE PROGRAM OF SCIENTIFIC INITIATION (SI), EMPHASIZING THE IMPORTANCE OF THE DAILY EXPERIENCE IN SCIENTIFIC RESEARCH. AN EXPERIENCE REPORT, WITH A DESCRIPTIVE METHOD, BASED ON THE EXPERIENCE OF BEING PART OF A RESEARCH GROUP WORKING AT THE LABORATORY OF HUMAN MOVEMENT ANALYSIS - UNIVERSIDAD EVANGELICAL DE GOIS. THE SCIENTIFIC INITIATION PROGRAMS ENABLE PARTICIPATION IN THE LABORATORY WHERE THERE IS CONTACT WITH PATIENTS WITH VARIOUS PATHOLOGIES AND DIFFERENT CONDITIONS, STUDENTS HAVE DEALT WITH CHILDREN, THE ELDERLY, VISUALLY AND HEARING IMPAIRED, AUTISTIC AND DOWN SYNDROME PATIENTS. THE SI STUDENT’S ENTRY INTO THE ROUTINE OF A RESEARCH GROUP SUPERVISED BY A RESEARCHER GENERATES EXTRACURRICULAR LEARNING IN MANAGING THEIR TIME, EMOTIONALLY DEALING WITH THE PRESSURE OF BEING WITH A PATIENT, WHICH IN THE FUTURE WILL BE HIGHLY VALUED IN THE JOB MARKET AND IN THE ENVIRONMENT. OF RESEARCH WHERE HE CAN STAY IN HIS POSTGRADUATE STUDIES. IT IS IN THE DAILY LIFE OF THE LABORATORY THAT THE STUDENT EXPERIENCES RESEARCH, ENCOUNTERS THE FIRST UNFORESEEN EVENTS OF THE RESEARCH, BUT THERE IS ALSO PROFESSIONAL AND PERSONAL GROWTH. THE EXPERIENCE IN THE LABORATORY AS A SI STUDENT, IF TAKEN WITH DEDICATION, CAN TEACH THE STUDENT ABOUT ADMINISTRATION, ORGANIZATION, EMOTIONAL INTELLIGENCE, HOW TO DEAL WITH PEOPLE, IN ADDITION TO THE RESEARCH ITSELF, WHERE HE LEARNS TO SEARCH FOR SOURCES OF STUDY EFFECTIVE, LEARNS TO DO AND WRITES HIS FIRST ARTICLES AND PRESENTS HIS FIRST WORKS, BEING ABLE TO DEMONSTRATE A PROMISING VOCATION FOR THE AREA OF €‹€‹RESEARCH.